A look at LOANSOME DOC service. - Lovas, I (1994)
The Pacific Southwest Regional Medical Library (PSRML) launched a project in 1988 to assess the feasibility of electronic linkages between health professionals using GRATEFUL MED--the National Library of Medicine's (NLM) software program for searching the MEDLARS databases--and libraries using DOCLINE, NLM's automated interlibrary loan request-and-referral system. This paper describes the origins of LOANSOME DOC and initial usage experiences. Results of the LOANSOME DOC beta test, including usage statistics, are reported. The paper also describes the mechanics of nationwide implementation of LOANSOME DOC, including guidelines used by the Regional Medical Libraries (RMLs) to refer unaffiliated health professionals to DOCLINE libraries for LOANSOME DOC service. National usage statistics for the first full year of implementation (October 1, 1991, to September 30, 1992) are provided, and user satisfaction surveys conducted in 1993 by two RMLs are examined. Future enhancements to LOANSOME DOC are suggested.